HIV-1 Vpu antagonizes CD317/tetherin by adaptor protein-1-mediated exclusion from virus assembly sites - Pujol, Franc̦ois; Laketa, Vibor; Schmidt, Florian; Mukenhirn, Markus; Müller, Barbara; Boulant, Steeve; Grimm, Dirk; Fackler, Oliver Till (Journal of virology, 2016)
The host cell restriction factor CD317/tetherin traps virions at the surface of producer cells to prevent their release. The HIV-1 accessory protein Vpu antagonizes this restriction. Vpu reduces the cell surface density of the restriction factor and targets it for degradation; however, these activities are dispensable for enhancing particle release. Instead, Vpu has been suggested to antagonize CD317/tetherin by preventing recycling of internalized CD317/tetherin to the cell surface, blocking anterograde transport of newly synthesized CD317/tetherin, and/or displacing the restriction factor from virus assembly sites at the plasma membrane. At the molecular level, antagonism relies on the physical interaction of Vpu with CD317/tetherin. Recent findings suggested that phosphorylation of a diserine motif enables Vpu to bind to adaptor protein 1 (AP-1) trafficking complexes via two independent interaction motifs and to couple CD317/tetherin to the endocytic machinery. Here, we used a panel of Vpu proteins with specific mutations in individual interaction motifs to define which interactions are required for antagonism of CD317/tetherin. Impairing recycling or anterograde transport of CD317/tetherin to the plasma membrane was insufficient for antagonism. In contrast, excluding CD317/tetherin from HIV-1 assembly sites depended on Vpu motifs for interaction with AP-1 and CD317/tetherin and correlated with antagonism of the particle release restriction. Consistently, interference with AP-1 function or its expression blocked these Vpu activities. Our results define displacement from HIV-1 assembly sites as active principle of CD317/tetherin antagonism by Vpu and support a role of tripartite complexes between Vpu, AP-1, and CD317/tetherin in this process. IMPORTANCE CD317/tetherin poses an intrinsic barrier to human immunodeficiency virus type 1 (HIV-1) replication in human cells by trapping virus particles at the surface of producer cells and thereby preventing their release. The viral protein Vpu antagonizes this restriction, and molecular interactions with the restriction factor and adaptor protein complex 1 (AP-1) were suggested to mediate this activity. Vpu modulates intracellular trafficking of CD317/tetherin and excludes the restriction factor from HIV-1 assembly sites at the plasma membrane, but the relative contribution of these effects to antagonism remain elusive. Using a panel of Vpu mutants, as well as interference with AP-1 function and expression, we show here that Vpu antagonizes CD317/tetherin by blocking its recruitment to viral assembly sites in an AP-1-dependent manner. These results refine our understanding of the molecular mechanisms of CD317/tetherin antagonism and suggest complexes of Vpu with the restriction factor and AP-1 as targets for potential therapeutic intervention.
Gesehen am 19.11.2018